Online condition monitoring of lithium ion batteries by performing impedance spectroscopy using a DC-DC converter - Moore, Sean (Department of Electrical Engineering, 2019)
Li-Ion batteries are currently being used extensively in a variety of applications such as portable electronics, electric vehicles and grid storage applications, due to the high demand for high power and high energy density storage batteries. However, the usage of Li-Ion batteries requires extensive condition monitoring to increase overall performance and life expectancy. This research is focused on implementing rapid online condition monitoring techniques, using signal injection via the associated power converter in the battery management system. The technique implemented in this work is known as Electrochemical Impedance Spectroscopy (EIS). EIS is a well-known technique, that has been used to characterize an electrochemical cell’s behaviour and state by monitoring changes in the cell's impedance. This is accomplished by injecting currents at different frequencies into the battery and measuring the voltage response. This technique is conventionally implemented, using standard Frequency Response Analysers (FRA), while the battery is disconnected from the load (offline) due to the long procedural times involved. This has limited the use of EIS to laboratory testing. In recent years, there has been literature regarding incorporating EIS testing into the battery system, which is done in mainly 2 ways, by including a linear amplifier into the system to inject the current perturbations directly, or by using the existing circuitry in the BMS (typically the DC-DC converter) to inject the current perturbations using various control techniques. Although, these strategies have been applied in literature for online systems, they are still riddled with a lengthy EIS measurement time issue. This work seeks to significantly reduce the associated testing time with the use broadband signals to implement Impedance Spectroscopy for online systems via the associated BMS converter. Broandband Impedance Spectroscopy (BIS) is implemented by injecting a signal with multiple frequencies concurrently as this allows for quicker measurement. The main contribution of this work is the real-time implementation of a multi-sine broadband excitation via a bi-directional converter that can be used in a varying system. The results obtained were compared to results from an industry standard FRA and showed to produce Nyquist plots with a reasonable error.